Kesesuaian Pemikiran dan Amalan Mazhab Selain Syafi’i dalam Masyarakat Islam di Malaysia: Satu Analisis Awal - Man, Saadan; Ali, Abdul Karim; Hj Abdullah, Luqman; Ramli, Rushdi; Ahmad farid, Inarah (Jurnal Fiqh, 2009)
The influence of Syafi’i madhdhab is deeply entrenched in Malay Muslim society since the advent of Islam to the Malay world. The Malay Muslims` attachment to the madhdhab is regarded as a sacrosanct tradition and it has never been contested until the emergence of Islamic reform movement in about a century ago. Among their major themes of reform is an idea called ?borderless fiqh? which is viewed as an attempt to break the domination of Syafi’i madhhab in Malay world. This attempt has resulted in controversy among scholars as well as among the Muslim community who view it as a kind of heresy and does not suit the common norms of Malaysian Muslim society. This paper aims at analysing the claim that the teachings of Islamic reform, particularly in this issue, are not suitable for Malays Muslim society. It also identifies the reality and issues revolving holding to a sole madhhab among the community. This paper is based on research which undertook several methods, mainly observations and interviews with scholars and those who hold religious authority. The research finds that, to some extent, the openess to other madhhabs is considered by many as one of a main factor that contributes to division among muslim community in Malaysia and thus threathens their harmonic religious life. However, reform is still necessary in order to induce religious awareness among the community, on a condition that it should be undertook by proper manners and appropriate approaches that suit to the reality of Malaysian Muslim society.